Epidemiological Dynamics and Trends of Dengue Outbreaks in Sao Tome and Principe: A Comprehensive Retrospective Analysis (2022–2024) - Sousa Lazaro; Vilfrido Santana Gil; Ivando Carvalho Viegas de Ceita; Isaulina Neto Viegas Barreto; Eula Carvalho Batista Sousa Maquengo; Andreza Batista de Sousa; Bakissy da Costa Pina; Tieble Traore; Alimuddin Zumla; John Otokoye Otshudiema (Tropical Medicine and Infectious Disease)
Background: Dengue has emerged as a significant public health concern in Sao Tome and Principe, with the first documented outbreak occurring between 2022 and 2024. This study examined the epidemiological patterns, environmental determinants, and demographic characteristics of dengue transmission during this period. Methods: We conducted a comprehensive retrospective analysis of laboratory-confirmed dengue cases using national surveillance data, clinical records, and environmental monitoring data. Statistical analyses included demographic profiling, temporal trend assessment, and environmental correlation studies using multiple regression modeling. Results: Among 1264 laboratory-confirmed cases, we observed distinct age-specific vulnerability patterns, with the highest incidence rate in the 70–79 age group (829.6 per 100,000) despite most cases occurring in younger adults. Rainfall emerged as the strongest predictor of dengue transmission (r = 0.96, p < 0.001), explaining 92% of case variance in the regression model. Case distribution showed marked temporal variation, with 91.9% of cases reported in 2022, coinciding with exceptional rainfall (3205 mm). The overall case fatality rate was 0.71% (95% CI: 0.33–1.35), with significant quarterly variations. Geographical analysis revealed concentration in the Água Grande district (68.2% of cases). Conclusions: This first comprehensive analysis of dengue in Sao Tome and Principe demonstrates the crucial role of rainfall in disease transmission and reveals important age-specific vulnerability patterns. These findings provide an evidence base for developing targeted interventions, particularly during high-rainfall periods, and suggest the need for age-stratified clinical protocols in similar island settings.